2004
DOI: 10.1126/science.1098252
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in Ultrathin Perovskite Films

Abstract: Understanding the suppression of ferroelectricity in perovskite thin films is a fundamental issue that has remained unresolved for decades. We report a synchrotron x-ray study of lead titanate as a function of temperature and film thickness for films as thin as a single unit cell. At room temperature, the ferroelectric phase is stable for thicknesses down to 3 unit cells (1.2 nanometers). Our results imply that no thickness limit is imposed on practical devices by an intrinsic ferroelectric size effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
802
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,201 publications
(881 citation statements)
references
References 26 publications
48
802
6
1
Order By: Relevance
“…This is consistent with experimental XRD results for PbTiO 3 films of similar thickness [31,32] and PbTiO 3 /SrTiO 3 superlattices [19,33,34]. Morphologically, these are LandauLifshitz domains having 90 • closure domain caps at the surface as previously observed in theoretical studies of PbTiO 3 films using interatomic potentials [11,35].…”
Section: Aa Domainssupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with experimental XRD results for PbTiO 3 films of similar thickness [31,32] and PbTiO 3 /SrTiO 3 superlattices [19,33,34]. Morphologically, these are LandauLifshitz domains having 90 • closure domain caps at the surface as previously observed in theoretical studies of PbTiO 3 films using interatomic potentials [11,35].…”
Section: Aa Domainssupporting
confidence: 80%
“…For films using a s = 3.99Å at 25 K the law is satisfied for N z ≥ 5 (001)PbO layers (2 nm) which returns a periodicity of 4.0 nm in agreement with experiment [31]. For thinner films the out-of-plane components of polarisation vanishes [32] but we observe that ferroelectricity is maintained with the polarisation reorientated in-plane (a-domain). Such reorientation has also been shown for PbTiO 3 films using DFT [36].…”
Section: Aa Domainssupporting
confidence: 66%
“…6,7,8 Furthermore, Fong et al showed that ferroelectric phases can be stable down to ∼12Å (three unit cells) in PbTiO 3 films by forming 180 • stripe domains, suggesting that no fundamental thickness limit is imposed by the intrinsic size effect in thin films. 9 This idea has been corroborated by ab initio calculations carried out on perovskite films, which tell that no critical thickness exists for polarization parallel to the surface 10 and that polarization perpendicular to the surface can exist in films three unit-cells thick if the depolarization field is artificially removed. 11,12 On the other hand, it has been found that the depolarization field plays a dominant role in reducing polarization normal to the surface and depressing ferroelectric transition temperatures in thin films.…”
mentioning
confidence: 60%
“…[[qv: 166c]],170 However, most studies are focused on thin‐film ferroelectric materials. As predicted, 1D ferroelectric nanostructures, where the unit cell and its corresponding ferroelectric/piezoelectric properties are supposed to be significantly influenced by the surface effect,171 might bring considerable advances to the research of FE‐PV devices. In 2015, Fei at al 71.…”
Section: Properties and Applicationsmentioning
confidence: 83%